MENINGKATKAN KEMAMPUAN MENYIMAK MELALUI KEGIATAN BERCERITA DENGAN MEDIA GAMBAR SERI - Adiyani, Tri Rahayu (JIV-Jurnal Ilmiah Visi, 2013)
This study aims to improve listening skills through storytelling with seriial picture mediua fo thechildren aged 4-5 years in Harapan Jaya kindergarten, North Jakarta. The study conducted in November and December 2012 apllied action research approach in two cycles, Each cycle consisted of planning, action, observation, and reflecting with ten children having listening problems as the subjects. The data collection techniques used were test and non test and analysis techniques used use the percentage increase. At the end of the second cycle it was discovered that the use of storytelling with serial picture media can improve listening skills of the children aged 4-5 years. The implications of this research is using serial pictures can be used as an alternative learning activities to improve the listening skills. The implementation of storytelling with serial pictures can give new and precious experiences to the children and motivate the to actively involve in learning activity.